Faktor-faktor yang berhubungan dengan kejadian hipertensi tidak terkontrol pada pasien prolanis - Oktavio, Irda Angelica; Suwito, Suwito; Aryastuti, Nurul; Sari, Fitri Eka (JOURNAL OF Qualitative Health Research & Case Studies Reports, 2025)
Background: The number of hypertension cases at the Gisting Community Health Center in 2024 was 1.164 people with hypertension. Of these, 120 individuals with hypertension were also participating in the chronic disease management program (Prolanis). Purpose: To determine factors associated with the occurrence of uncontrolled hypertension in Prolanis patients at the Gisting Community Health Center in 2024. Method: This was a quantitative analytical study with a cross-sectional design. The sample consisted of 120 hypertensive patients participating in the Prolanis program at the Gisting Community Health Center in 2024. Data collection was conducted using a questionnaire. Data analysis was conducted using the chi-square test and logistic regression. Results: There is no relationship between smoking and uncontrolled hypertension with p value: 0.198; there is no relationship between stress and uncontrolled hypertension with p value: 0.236; there is a relationship between adherence to antihypertensive medication consumption and uncontrolled hypertension with p value: 0.000; OR: 14.760; there is a relationship between routine check-ups and uncontrolled hypertension with p value: 0.0.000; OR: 17.862; there is a relationship between a history of diabetes mellitus and uncontrolled hypertension with p value: 0.022; OR: 2.799; there is no relationship between total cholesterol levels and uncontrolled hypertension with p value: 0.062; the most dominant factor is routine check-ups with OR value: 8.362. Conclusion: There is no relationship between smoking and uncontrolled hypertension, there is no relationship between stress and uncontrolled hypertension, there is a relationship between adherence to antihypertensive medication consumption and uncontrolled hypertension, there is a relationship between routine check-ups and uncontrolled hypertension, there is a relationship between a history of diabetes mellitus and uncontrolled hypertension, there is no relationship between total cholesterol levels and uncontrolled hypertension, and the most dominant factor is routine check-ups.   Keywords: Uncontrolled Hypertension; Prolantis.   Pendahuluan: Jumlah kasus hipertensi di Puskesmas Gisting pada tahun 2024 yaitu sebanyak 1.164 orang yang terkena hipertensi. Didapatkan sejumlah 120 orang yang memiliki penyakit hipertensi juga mengikuti program pengelolaan penyakit kronis (Prolanis). Tujuan: Untuk mengetahui faktor-faktor yang berhubungan dengan kejadian hipertensi tidak terkontrol pada pasien Prolanis di Puskesmas Gisting Tahun 2024. Metode: Penelitian analitik kuantitatif dengan desain cross-sectional. Sampel penelitian adalah penderita hipertensi yang mengikuti program Prolanis di Puskesmas Gisting Tahun 2024 sebanyak 120 orang. Teknik pengumpulan data menggunakan kuesioner. Teknik analisis data menggunakan uji chi-square dan regresi logistic. Hasil: Tidak ada hubungan merokok dengan hipertensi tidak terkontrol dengan p value: 0.198; tidak ada hubungan stress dengan hipertensi tidak terkontrol dengan p value: 0.236; ada hubungan kepatuhan konsumsi obat antihipertensi dengan hipertensi tidak terkontrol p value: 0.000; OR: 14.760; ada hubungan pemeriksaan rutin dengan hipertensi tidak terkontrol p value: 0.000; OR: 17.862; ada hubungan riwayat diabetes mellitus dengan hipertensi tidak terkontrol dengan p value: 0.022; OR: 2.799; tidak ada hubungan kadar kolesterol total dengan hipertensi tidak terkontrol dengan p value: 0.062; faktor yang paling dominan adalah pemeriksaan rutin dengan nilai OR: 8.362. Simpulan: Tidak ada hubungan merokok dengan hipertensi tidak terkontrol, tidak ada hubungan stress dengan hipertensi tidak terkontrol, ada hubungan kepatuhan konsumsi obat antihipertensi dengan hipertensi tidak terkontrol, ada hubungan pemeriksaan rutin dengan hipertensi tidak terkontrol, ada hubungan riwayat diabetes mellitus dengan hipertensi tidak terkontrol, tidak ada hubungan kadar kolesterol total dengan hipertensi tidak terkontrol, dan faktor yang paling dominan adalah pemeriksaan rutin.   Kata Kunci: Hipertensi Tidak Terkontrol; Prolanis.